Parallels and contrasts - Wendezeit in South African and German literature - P. Horn (Literator, 1997)
We live in the present, but our language is always the language of the past. Memory is fragile, evanescent and often distorted. Even where memories are vivid and subjectively compelling, there is no guarantee that they are correct. The documents which come down to us are riddled with lacunae, silences, and with outright lies. But these documents are the basis and the limit of our constant rewriting of history. Official history is an erasure of an alternative history. The truth, which surfaces in myths and stories, is the truth forgotten by history, or more precisely, the truth repressed by history. Not only the henchmen and the prison warders have a bad memory. The victims, too, have difficulties remembering. But not to want to know the truth about oneself is an attitude which always leads to catastrophe. Literature discovers the dark underworld beneath the glittering surface of this country, which considers itself to be happy. It is art, the novel, the poem, the image, which transcends the boundary of that area which is excluded from language. Fictional reports can, however, do that only because they lack the authority of official history writing, because that which is written fictionally has been called a lie since the time of Plato. There is, nevertheless, a silence underneath the rationality of the historical method, an unknown.